2009
DOI: 10.21608/eajbsa.2009.15500
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and biochemical studies of Methylamine Avermactin, a new type of bioinsecticide against the cotton leafworm, Spodoptera littoralis (Biosd).

Abstract: Larvicidal efficacy of a new semi-synthetic avermectin derivative Methylamine avermectin (Radical 0.5% EC) was determined against larval instars of the Egyptian cotton leafworm, Spodoptera littoralis (Biosd.) in the laboratory, field and semi field experiments. 2 nd and 4 th instar larvae showed greatest susceptibility to the Radical in the laboratory experiment. The LC 50s values of the 2 nd and 4 th larval instar after 48 hours were 0.005 and 0.008 ppm, respectively. Radical was tested with recommended dosag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…These results showed that there were significant differences between the effect of the three tested insecticides and control. The present results agreed with that recorded by Abdel-Aal, 2006 andDahi et al, 2009 who recorded inhibition effect of chlorfluzuron and methylamine avermactinon total carbohydrate of S. littoralis. Also, El-Sheikh, 2012 state that the total carbohydrates content in 6 th larval instar treated with spinosad significantly decreased.…”
Section: Field and Semi-field Studiessupporting
confidence: 94%
“…These results showed that there were significant differences between the effect of the three tested insecticides and control. The present results agreed with that recorded by Abdel-Aal, 2006 andDahi et al, 2009 who recorded inhibition effect of chlorfluzuron and methylamine avermactinon total carbohydrate of S. littoralis. Also, El-Sheikh, 2012 state that the total carbohydrates content in 6 th larval instar treated with spinosad significantly decreased.…”
Section: Field and Semi-field Studiessupporting
confidence: 94%
“…The disturbance in carbohydrate was expressed by impairments in the activity of carbohydrate enzymes in treated larvae. Similar observation in S. littoralis has also been reported by several investigators (Radwan et al 1984;Eid, 2002;El-Barky et al, 2008;Dahi et al, 2009 andRashwan, 2013). In insects, as in other animals, the transaminases (GOT and GPT) are key enzymes in the formation of nonessential amino acids, in metabolism of most nitrogenous products and in glucogenesis (Tanani et al, 2009).…”
Section: Littoralissupporting
confidence: 88%
“…GST fluctuations could be the outcome of abnormalities in the functioning of the insect detoxificative system as consequences of the biopesticide treating. These fluctuations and the abnormal functions of GST can increase the sensitivity of the treated insects as noted by (Dubovskiy et al, 2008 andDahi et al, 2009) mentioned that the application of biopesticides guides to decline in the Acetylecholinsterase activity because of the sensitivity of insects to biopesticides, or guides to its rise because of the novel mode of action of recently biopesticides. Reduction in GST activity during the infection at 24-48h of nematodes may be associated with effective inhibition of the host defense systems by entomopathogenic nematodes.…”
Section: Resultsmentioning
confidence: 99%